2011
DOI: 10.4103/1319-3767.82587
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous appendicitis

Abstract: Gastrointestinal tuberculosis is quite rare, representing only 3% of all extrapulmonary cases. Involvement of the appendix is rare, only occurring in about 1% of cases. It is usually secondary to tuberculosis elsewhere in the abdomen. A prompt diagnosis depends on a high index of suspicion as clinical signs may be nonspecific and microbiological confirmation is difficult. Histopathologic examination is often the only way to reach a diagnosis and to establish specific antibiotic therapy. In these cases, due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…Several authors reported the mode of tuberculous appendicitis infection to be ingestion of contaminated foods and unhealthy sanitary habits. 3 , 6 Rabbani et al 7 reported that tuberculous appendicitis was usually secondary to TB elsewhere in the abdomen. 7 Sinha and Sarin 8 also reported that appendicular TB was associated with secondary tuberculous salpingitis.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported the mode of tuberculous appendicitis infection to be ingestion of contaminated foods and unhealthy sanitary habits. 3 , 6 Rabbani et al 7 reported that tuberculous appendicitis was usually secondary to TB elsewhere in the abdomen. 7 Sinha and Sarin 8 also reported that appendicular TB was associated with secondary tuberculous salpingitis.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had a subacute onset. Other published cases showed different types of onset of TB appendicitis, either acute, moreover with classical appendicitis signs [11], or subacute, the rarest, with appendiceal mass, often treated for acute gastroenteritis [12]. Most frequent symptoms cited are weight loss, weakness, lack of appetite, along with uncharacteristic abdominal pain, as our patient [13].…”
Section: Discussionmentioning
confidence: 55%
“…TB may affect all of the segments of the GI system, from the mouth to anus with ileo-cecal involvement of 40% of cases of intra-abdominal tuberculosis [23]. Tubercular appendicitis was first recognized by Corbin in 1873 and seen in about 1% of cases of intra-abdominal appendicitis [23,24]. Histopathological examination is usually needed for accurate diagnosis of this condition and usually reveals the presence of caseating granulomas and Langhans giant cells.…”
Section: Discussionmentioning
confidence: 99%